Chuyển đổi số trong kinh tế phi chính thức: Các yếu tố quyết định áp dụng bán lẻ đa kênh của tiểu thương tại chợ truyền thống ở Đà Nẵng, Việt Nam - Đặng Thị Thu, Trang; Phạm Thảo, Nguyên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
Digital transformation is becoming an urgent imperative for the informal economy, particularly for traditional market vendors facing intense competitive pressure from e-commerce. However, the factors driving this “vulnerable” group to adopt multi-channel retailing - a critical initial step in the digital transformation process - remain unclear. This study addresses this gap by developing and validating an integrated model based on three foundational theories (TPB, TAM, and TOE) using survey data from 457 traditional market vendors. PLS-SEM analysis results indicate that Attitude plays a central role, serving not only as the strongest direct predictor of intention but also as a vital mediating mechanism that translates technological perceptions (perceived ease of use, perceived usefulness) into behavioral intent. Notably, environmental factors, specifically Government support and competitive pressure, are identified as significant exogenous motivators. The findings suggest developing on-site training programs and designing “accessible and user-friendly” technological solutions to promote successful digital transformation in traditional markets.